ON THE MORALITY OF GUINEA-PIG RECRUITMENT - Valdman, Mikhail (Bioethics, 2010)
Can it be wrong to conduct medical research on human subjects even with their informed consent and even when the transaction between the subjects and researchers is expected to be mutually beneficial? This question is especially pressing today in light of the rise of a semi-professional class of ‘guinea pigs’– human research subjects that sell researchers a right of access to their bodies in exchange for money. Can these exchanges be morally problematic even when they are consensual and mutually beneficial? I argue that there are two general kinds of concern one can have about such transactions – concerns about the nature of what is sold and concerns about the conditions in which the selling occurs. The former involves worries about degradation and the possible wrongness of selling a right of access to one's body. These worries, I argue, are not very serious. The latter involves worries about coercion, exploitation, and undue influence – about how, by virtue of their ignorance, impulsiveness, or desperation, guinea pigs can be taken advantage of by medical researchers. These worries are quite serious but I argue that, at least in cases where the exchange between guinea pigs and researchers is consensual and mutually beneficial, they do not raise insurmountable moral problems.